(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
This paper proposes a new version of the Reve’s puzzle, allowing at most one violation of the “divine rule”. Letting S(n) be the minimum number of moves required to solve the problem with n(³ 1) discs, an scheme is given to find the dynamic programming equation satisfied by S(n). A closed- form expression of S(n) is derived. J. Bangladesh Acad. Sci. 46(2); 213-217 December 2022